Perancangan Sistem Pendukung Keputusan Pengendalian Persediaan Obat Gawat Darurat Prioritas I di RSUD Dr. Moewardi Surakarta - Azizah Aisyati; Muh. Hisjam; Miftakhul Arfah Hadiani (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2007)
RSUD DR Moewardi is a state hospital of central Java Province in Surakarta which gives health service. One of the important facilities in this hospital is the pharmacy division. Some of its duties are to order, to plan, and to control drugs inventory. There are 1200 types of drugs that divided into emergency drug and non emergency drug. The Emergency Drugs (ED) function is as life saving that divided into 1 st priority, 2 nd priority and 3 rd priority ED. The 1 st priority ED are the 57 drugs that have highest management level and don’t have an emptiness tolerance. In the drug inventory control, the hospital hasn’t applied a certain drugs inventory control system. The ordering system is only based on the planning without considering the onhand status. This condition causes an overstock or even a stock out. Beside that, the drugs have an expired date. When it almost expired in 3 months later, it must be exchanged to PBF. Sometimes the tardiness happens in the hospital. Therefore it needs the Decision Support System(DSS) aim to give an early warning to exchange the drugs that are almost expired in 3 months later and also to determine the order quantity and period. First phase is designing of model base using hybrid inventory control system that combined reorder point (ROP) and periodic review system. The second phase is designing of data base using normalization and entity relationship diagram. The last phase is designing of user interface covering input and output process. From examination result, this DSS can determine the order quantity and period and also give an early warning to exchange the drugs that are almost expired in 3 months later.